Strategic intelligence and its relationship to decision-making among administrative and academic leaderships - ALZahrani, ALShaimaa Khalid; ALEssa, Ghuzayyil Saad (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the requirements of applying strategic intelligence, its importance, and its role in the administrative decision-making process, the extent of the relationship between it’s elements in decision-making processes, using the method Descriptive. The study sample reach (201) from all the administrative and academic leaderships in three government agencies (the National Water Company, the General Organization for Technical and Vocational Training, and KSU) in Riyadh. The results showed approval of the proposed requirements for applying strategic intelligence with average (4.13), which the most important of which were the training courses that help the administration in improving the application of strategic intelligence also approval of its role in the administrative decision-making with average (4.1) in addition the existence of a relationship between the elements of strategic intelligence in the administrative decision-making process, also there are no statistically significant differences between strategic intelligence and the characteristics of the study sample; According to academic qualification and work point, while there are statistically significant differences in the requirements of applying strategic intelligence; According to qualification, employer. finally study recommended holding training courses for leaderships. On the concepts of strategic intelligence and its importance in making decision.